Pengajaran Membaca Melalui Pendekatan Kognitif dan Konstruktivisme - Sumita Sabilla; Suci Mutiara Fitriah Lubis; Fauziah Nasution (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Some features of the communicative approach, such as the use of authentic learning materials, the emphasis on the significance (meaning) rather than form (form) language, and the use of interaction in the learning process of students are still relevant to the purpose of mastering Arabic overall as a tool to communicate. However, in the world of teaching in general has developed several alternative approaches, which one of them is the constructivist and cognitive approach. In this article, the author will introduce a model for the application of constructivist approaches in teaching Arabic as a foreign language, especially for the teaching of reading. Key words : Learning of Reading, Constructivist approach, Cognitive approach